Single-Ion Implantation for the Development of Si-Based MOSFET Devices with Quantum Functionalities. (28th November 2011) - McCallum, Jeffrey C.; Jamieson, David N.; Yang, Changyi; Alves, Andrew D.; Johnson, Brett C.; Hopf, Toby; Thompson, Samuel C.; van Donkelaar, Jessica A.
Abstract : Interest in single-ion implantation is driven in part by research into development of solid-state devices that exhibit quantum behaviour in their electronic or optical characteristics. Here, we provide an overview of international research work on single ion implantation and single ion detection for development of electronic devices for quantum computing. The scope of international research into single ion implantation is presented in the context of our own research in the Centre for Quantum Computation and Communication Technology in Australia. Various single ion detection schemes are presented, and limitations on dopant placement accuracy due to ion straggling are discussed together with pathways for scale-up to multiple quantum devices on the one chip. Possible future directions for ion implantation in quantum computing and communications are also discussed.